Stimulation of metacyclogenesis in Leishmania (Mundinia) orientalis for mass production of metacyclic promastigotes - Chanmol, Wetpisit; Jariyapan, Narissara; Preativatanyou, Kanok; Mano, Chonlada; Tippawangkosol, Pongsri; Somboon, Pradya; Bates, Paul A. (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania (Mundinia) orientalis is a human pathogen causing leishmaniasis and studies on the properties of metacyclic promastigotes, the parasite's infective stage, are required for a better understanding of its transmission and infection. However, information on cultivation for mass production of L. orientalis metacyclic promastigotes and factors that stimulate their metacyclogenesis is limited. Therefore, the objective of this study was to develop a suitable methodology for generating promastigote cultures containing a high proportion and number of L. orientalis metacyclic promastigotes. Various media, i.e., Schneider's insect medium, Medium 199 and Grace's insect medium, supplemented with various quantities of dithiothreitol, Basal Medium Eagle vitamins, pooled human urine, and fetal bovine serum, were optimized for metacyclogenesis. The results revealed that the optimum culture medium and conditions of those tested were Schneider’s insect medium supplemented with 100 μM dithiothreitol, 1% (v/v) Basal Medium Eagle vitamins, 2% (v/v) pooled human urine, and 10% (v/v) fetal bovine serum, pH 5.0 at 26 °C. We also demonstrated that L. orientalis metacyclic promastigotes could be purified and enriched by negative selection using peanut lectin. Under these culture conditions, the highest yield of metacyclic promastigotes was obtained with a significantly higher percentage of parasite survival, resistance to complement-mediated lysis, and infection index in THP-1 macrophage cells compared to parasites cultured without media supplements at neutral pH. This is the first report providing a reliable method for mass production of L. orientalis metacyclic promastigotes for in vivo infections and other experimental studies of this emerging parasite in the future.